Efficient Production of 2,5-Diketo-D-gluconic Acid by Reducing Browning Levels During Gluconobacter oxydans ATCC 9937 Fermentation - Li, Guang; Shan, Xiaoyu; Zeng, Weizhu; Yu, Shiqin; Zhang, Guoqiang; Chen, Jian; Zhou, Jingwen (Frontiers in Bioengineering and Biotechnology, 2022)
D-Glucose directly generates 2-keto-L-gulonic acid (2-KLG, precursor of vitamin C) through the 2,5-diketo-D-gluconic acid (2,5-DKG) pathway. 2,5-DKG is the main rate-limiting factor of the reaction, and there are few relevant studies on it. In this study, a more accurate quantitative method of 2,5-DKG was developed and used to screen G. oxydans ATCC9937 as the chassis strain for the production of 2,5-DKG. Combined the metabolites profile analysis and knockout and overexpression of production strain, the non-enzymatic browning of 2,5-DKG was identified as the main factor leading to low yield of target compound. By optimizing the fermentation process, the fermentation time was reduced to 48 h, and 2,5-DKG production peaked at 50.9 g/L, which was 150.7% higher than in control group. Effectively eliminating browning and reducing the degradation of 2,5-DKG will help to increase the conversion of 2,5-DKG to 2-KLG, and finally establish a one-step D-glucose to 2-KLG fermentation pathway.